Hepatic decompensation during paritaprevir/ritonavir/ombitasvir/dasabuvir treatment for genotype 1b chronic hepatitis C patients with advanced fibrosis and compensated cirrhosis. - Yi-Chung Hsieh; Wen-Juei Jeng; Chien-Hao Huang; Wei Teng; Wei-Ting Chen; Yi-Cheng Chen; Shi-Ming Lin; Dar-In Tai; Chun-Yen Lin; I-Shyan Sheen (PLoS ONE, 2018)
BACKGROUND AND AIM:Hepatic decompensation is a severe on-treatment adverse event for chronic hepatitis C treated with paritaprevir/ritonavir/ombitasvir and dasabuvir (PrOD). Till now, few papers regarding on-treatment hepatic decompensation have been reported. The study aims to analyze the general feature and predictive factors of on-treatment hepatic decompensation in hepatitis C virus (HCV) genotype 1b-infected patients with advanced fibrosis and compensated cirrhosis who receive treatment with PrOD. METHODS:A real-word cohort enrolled 189 HCV genotype 1b patients with advanced fibrosis and compensated cirrhosis treated with 12-week PrOD. Clinical and laboratory data were analyzed between patients with and without on-treatment hepatic decompensation. RESULTS:The sustained virologic response rate at 12 weeks after treatment was 97.3% in HCV subtype 1b patients with advanced fibrosis and cirrhosis. On-treatment hyperbilirubinemia (total bilirubin >2 mg/dL) occurred in 27 (14.3%) patients, and the incidence of the increase of total and direct form bilirubin was significantly different during treatment between patients with Child-Turcotte-Pugh score 5 and score 6. Five (18.5%) hyperbilirubinemia patients progressed to hepatic decompensation. Older age (adjusted OR: 1.2, 95% CI: 1.0-1.4) and albumin ≤3.6 g/dL (adjusted OR: 10.4, 95% CI: 1.3-81.2) may be two predictors for on-treatment hepatic decompensation by multivariate analysis. CONCLUSIONS:PrOD is an effective direct-acting antiviral agent for antiviral therapy in HCV genotype 1b patients with advanced fibrosis and cirrhosis. Hyperbilirubinemia is possibly the early warning feature of on-treatment hepatic decompensation. This serious adverse event of on-treatment hepatic decompensation is not common. Older age and low baseline albumin level may be predictive factors.